Avoiding surgery in prostate cancer patients with low-risk disease. Issue 1 (January 2008) - Mouraviev, Vladimir; Polascik, Thomas J
At present, the treatment paradigm for localized prostate cancer (PCa) is to distinguish patients with clinically relevant cancers who require treatment either in the form of traditional radical therapy or a contemporary less aggressive, organ-preserving approach, from the remainder who do not need any intervention at the time of diagnosis. Recent research has proposed a rationale for an active surveillance (AS) strategy with deferred definitive therapy in a select cohort of patients with low-risk PCa; however, this approach requires careful patient selection, regular long-term follow-up and the possibility of altering treatment towards a more aggressive modality. For another select group of patients with unifocal or unilateral PCa, alternative treatment options may include focal therapy or subtotal glandular ablation with cryotherapy, for example, as a more established and proven technique. Other potential minimally invasive procedures that are nonsurgical in nature that can also be utilized in the clinical arena include high-intensity focused ultrasound, or vascular-targeted photodynamic therapy, which is currently undergoing clinical study. However, additional basic science research and large-scale randomized clinical trials with long-term oncologic follow-up and quality of life outcomes are necessary before any conclusions can be made about the sustained efficacy of these minimally invasive options. This perspective article evaluates the current trends for treating localized, low-risk PCa in a nonsurgical fashion, and in particular to discuss focal therapy as a means of targeting the known cancer in select low-risk cases, thus avoiding whole-gland therapy and its inherent potential complications regarding quality of life. Traditional surgical, radiotherapy or hormonal therapeutic modalities are beyond the scope of this perspective article.